2005
DOI: 10.1002/wcm.242
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive evaluation of chip interleaving effect on turbo‐coded DS‐SS in a Rayleigh fading channel with antenna diversity reception

Abstract: In this paper, we present a comprehensive performance evaluation of chip interleaving effect on turbo coded direct sequence spread spectrum (DS-SS) system in a frequency non-selective Rayleigh fading channel with antenna diversity reception. At the transmitter, chip interleaver scrambles the SF (spreading factor) chips associated with a data symbol and transforms the transmission channel into a highly time-selective or highly memoryless channel at the chip level. The use of chip interleaving is equivalent to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…It is observed that the user-specific chip interleavers effectively enlarge the free distance of the channel code employed, and the resultant codewords of the different users constitute unique noiselike random signatures [3]. The employed chip interleaving is also capable of increasing the achievable time diversity in time-selective channels, where the burst errors are dispersed, and hence, the achievable decoding capability is improved [4]. Furthermore, IDMA is capable of striking the best tradeoff between the channel-coding rate and DSspreading factor, hence improving the attainable error resilience [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that the user-specific chip interleavers effectively enlarge the free distance of the channel code employed, and the resultant codewords of the different users constitute unique noiselike random signatures [3]. The employed chip interleaving is also capable of increasing the achievable time diversity in time-selective channels, where the burst errors are dispersed, and hence, the achievable decoding capability is improved [4]. Furthermore, IDMA is capable of striking the best tradeoff between the channel-coding rate and DSspreading factor, hence improving the attainable error resilience [5].…”
Section: Introductionmentioning
confidence: 99%